Адміністративно-правовий статус Національної поліції України як суб’єкта протидії домашньому насильству - Саббатовський, В. Ю.; Sabbatovskyi, V. Yu. (Юридичний науковий електронний журнал. - 2024. - № 2. - С. 294-298, 2024)
Розглянуто питання адміністративно-правового статусу Національної поліції як суб'єкта протидії домашньому насильству. Здійснено категоріальний аналіз понять, пов’язаних з проблемою протидії домашньому насильству, а саме: «адміністративно-правовий статус Національної поліції, «протидія домашньому насильству» «суб'єкт», «суб'єкт права», «суб'єкт протидії домашньому насильству». Встановлено неоднозначність тлумачення понять «протидія», «боротьба», «запобігання», «попередження», а також відсутність означення поняття "суб’єкт протидії домашньому насильству" у чинному законодавстві. Зроблено висновок про необхідність подальшого теоретичного осмислення, уточнення і належного обґрунтування категоріального апарату з означеної тематики. Проведено аналіз законодавчих та відомчих нормативно-правових актів, в результаті чого було з’ясовано адміністративно-правовий статусу Національної поліції України як суб’єкта протидії домашньому насильству, виокремлено проблемні аспекти та надано певні рекомендації і пропозиції в частині удосконалення чинного законодавства.

The article is devoted to consideration of the issue of the administrative and legal status of the National Police as a subject of combating domestic violence. It was established that, despite the modern regulatory and legal support in the field of combating domestic violence, as well as a significant number of scientific works devoted to various aspects in this field, the problem of domestic violence, the powers of the National Police as a subject of combating domestic violence does not lose its relevance. A categorical analysis of concepts related to the problem of combating domestic violence was carried out, namely: "administrative and legal status of the National Police, "combating domestic violence" "subject", "subject of law", "subject of combating domestic violence ". The ambiguity of the interpretation of the concepts of "counteraction", "fight", "prevention", "warning", as well as the absence of a definition of the concept of "the subject of combating domestic violence" in the current legislation was established. A conclusion was made about the need for further theoretical understanding, clarification and proper substantiation of the categorical apparatus on the given topic. An analysis of legislative and departmental normative legal acts was carried out, as a result of which the administrative and legal status of the National Police of Ukraine as a subject of combating domestic violence was clarified, problematic aspects were singled out and certain recommendations and suggestions were given in terms of improving the current legislation. It is noted that the bodies of the National Police of Ukraine act as a special subject of combating domestic violence. The authorized units of the National Police of Ukraine, which carry out prevention and countermeasures against domestic violence, include the Department of Preventive Activities of the National Police of Ukraine, the patrol service of the Ministry of Internal Affairs of Ukraine, juvenile prevention units and the service of precinct police officers, whose powers are reflected in legislative and departmental legal acts. At the same time, there is an inconsistency in the distribution of powers, responsibilities, action algorithms due to their definition by various regulatory and legal acts, multiple reorganization and transfer of powers, which complicates effective interaction between the subjects of combating domestic violence. Improvement of legal acts will increase the effectiveness of measures to counter this negative social phenomenon, and will allow, in our opinion, to more effectively counter domestic violence in Ukrainian society.

Рассмотрены вопросы административно-правового статуса Национальной полиции как субъекта противодействия домашнему насилию. Осуществлен категориальный анализ понятий, связанных с проблемой противодействия домашнему насилию, а именно: «административно-правовой статус Национальной полиции, «противодействие домашнему насилию»; «субъект», «субъект права», «субъект противодействия домашнему насилию ». Установлена неоднозначность толкования понятий «противодействие», «борьба», «предотвращение», «предупреждение», а также отсутствие определения понятия "субъект противодействия домашнему насилию" в действующем законодательстве. Сделан вывод о необходимости дальнейшего теоретического осмысления, уточнения и надлежащего обоснования категориального аппарата по данной тематике. Проведен анализ законодательных и ведомственных нормативно-правовых актов, в результате чего был выяснен административно-правовой статус Национальной полиции Украины как субъекта противодействия домашнему насилию, выделены проблемные аспекты и даны определенные рекомендации и предложения в части усовершенствования действующего законодательства.
Administrative and legal status of the National Police of Ukraine as a subject of combating domestic violence
Keywords: домашнє насильство; протидія домашньому насильству; суб’єкти протидії домашньому насильству; Національна поліція України; адміністративно-правовий статус; domestic violence; combating domestic violence; subjects of combating domestic violence; National Police of Ukraine; administrative and legal status; домашнее насилие; противодействие домашнему насилию; субъекты противодействия домашнему насилию; Национальная полиция Украины; административно-правовой статус